Foot allergic contact dermatitis to mixed dialkyl thioureas. Issue 4 (7th May 2019) - Rundle, Chandler W.; Funk, Tracy; Brockman, Ross M.; Schwarzenberger, Kathryn
Abstract: A 12‐year‐old boy presented with severe, bilateral foot dermatitis. Extended patch testing was performed, revealing a significant positive reaction to mixed dialkyl thioureas. A thorough review of his history revealed that he was likely being exposed through his neoprene taekwondo shoes. After implementation of allergen avoidance measures, his dermatitis resolved. This case emphasizes awareness of potential allergen exposures and offers helpful avoidance strategies.